The power of identity - Castells, Manuel (Malden Blackwell Pub, 2010)
In this second volume of The Information Age trilogy, with an extensive new preface following the recent global economic crisis, Manuel Castells deals with the social, political, and cultural dynamics associated with the technological transformation of our societies and with the globalization of the economy.
Includes bibliographical references (p. [466]-511) and index.
Keywords: Information society